'Social' egg freezing and the UK's statutory storage time limits. Issue 11 (23rd August 2016) - Jackson, Emily
Abstract : This article argues that the statutory time limits upon the storage of gametes have unintended and perhaps even perverse consequences for women freezing their eggs as insurance against age-related fertility decline. They work against good clinical practice and potentially represent an interference with a woman's right to respect for her family life, which is neither necessary nor proportionate. My claim will be that the statutory time limit, and the options for extension, are no longer fit for purpose.